Assessment of lateral pterygoid muscle and temporomandibular joint disc after Le Fort I osteotomy with and without intentional pterygoid plate fracture and sagittal split ramus osteotomy in class II and class III patients. Issue 1 (January 2022) - Ueki, Koichiro; Yoshizawa, Kunio; Takayama, Akihiro; Baba, Nana; Kimura, Yujiro; Koizumi, Mai; Fujimoto, Kana; Iguchi, Ran; Ono, Sumire; Osada, Asami Hotta; Moroi, Akinori
Abstract: The aim of the study was to examine lateral pterygoid muscle (LPM) and temporomandibular joint (TMJ) disc before and after Le Fort I osteotomy with and without intentional pterygoid plate fracture and sagittal split ramus osteotomy (SSRO) in class II and class III patients. Le Fort I osteotomy and SSRO were performed in class II and class III patients. LPM measurements using oblique sagittal computed tomography (CT) images and TMJ disc position using magnetic resonance imaging (MRI) were examined. Statistical comparisons were performed for the LPM and TMJ between class II and class III patients and between those with and without intentional pterygoid plate fracture in Le Fort I osteotomy. The subjects comprised 60 female patients (120 sides), with 30 diagnosed as class II and 30 as class III. Preoperatively, the width of the condylar attachment, width at eminence, length of the LPM, angle of the LPM, and square of the LPM were significantly smaller in the class II group than in the class III group ( p < 0.05). After 1 year, the width of the condylar attachment, width at eminence, and angle of the LPM remained significantly smaller in the class II group than in the class III group ( p < 0.0001). TMJ disc position was significantly related to the width of the condylar attachment of the LPM, both pre- and postoperatively ( p < 0.0001). However, postoperative disc position did not change in all patients. Next, the class II patients (60 sides) were divided into two groups who underwent Le Fort I osteotomy with or without intentional pterygoid plate fracture. Changes in all measurements of the LPM showed no significant differences between these two groups. Our study suggested that TMJ disc position classification could be associated with the width of condylar attachment of the LPM before and after surgery, while the surgical procedure, including Le Fort I osteotomy with intentional pterygoid plate fracture, might not affect postoperative LMP or disc position in class II patients.